A question of causality between political corruption, economic freedom and economic growth in Europe - Kuloglu Ayhan (Crisis Aftermath: economic policy changes in the EU and its Member States : International Conference University of Szeged 8-9 March 2012 : conference Proceedings, 2012)
Economic, cultural, social, psychological, political, administrative and religious effects of corruption are manifested by functional, political and moral degradation of local public authorities, which is a result of the expansion of political corruption, by reducing the transparent and accountable political power or by social tensions and increasing impoverishment of the population. In the executive activity, corruption has an effect on the reduced quality of public administration, the existence of an informal decision-making system and close links between organized crime, corrupt officials and politicians. Thus, outwardly effects of corruption, even in international relations, is manifested by the conduct of incompetent, irresponsible, provocative and subjective – conventional behavior of persons in positions of responsibility which, in dealing with foreign partners, primarily promotes personal and corporate interests against national interests, which, inevitably undermines the country's image and credibility as a partner in international relations. This paper tries to showa more accurate picture of the extent of corruption in Europe, through individual analysis of indicators measuring corruption and by quantifying the relation between corruption and political, administrative and economic determinants factors, through a regressive “pool data” model. For a fine approximation of the decision-making mechanism, in accordance with the policies they generate, there is a necessity the knowledge and understanding of how the political elements are transformed into real elements to measure their incidence. This paper adds to the empirical literature on the relationship between corruption and economic growth by incorporating the impact of economic freedom.